(Un)Natural Saviors and Motivators: Analyzing the Pathological Scripting of Black Male Teachers in Hollywood Films. Issue 4 (4th July 2022) - Thomas, Daniel; Johnson, Marcus; Brown, Anthony
Abstract: This article explores how Black male teachers in Hollywood films continue to be encoded with meanings derived from deficit social science discourse generated through a white-controlled epistemic order. Drawing from the framework of critical public pedagogy and utilizing the critical visual cultural tradition, we contend that the representation of Black male teachers on film is rooted in longstanding conceptual narratives of Black men and boys. Findings indicate that cinematic films both develop their scripts around and contextualize the necessity of Black male teachers within deficit sociological tropes of absent Black fathers and their endangered sons.